Agro-ecosystems simulation models as web services for using in web applications - Marcos, Martín (2016)
Agricultural system science includes the agricultural system models, the data needed to use them, and all the results for guiding deci-sions and policies. Modern cloud technologies can play an important role by providing effective interfaces for using these models. There are several websites that offer environmental data in real time. Some of these websites incorporate map-based geographical and environmental information such as weather forecasting and satellite imaginary. We im-plemented a simple environmental simulation model: the Web API-SWB Basic, as an experiment of accessing and executing agro-ecosystems models via a Web API. Our goal is to expand this model to a broader range of models that can be used for more comprehensive agro-ecosystems modeling like nutrient balances and cycling, carbon dynam-ics, rotations. The product would be a set of models, included in a sort of toolbox and used with Web APIs, that can be picked according to specific needs.